2012
DOI: 10.1021/jp208183p
|View full text |Cite
|
Sign up to set email alerts
|

Collision-Induced Dissociation of Halide Ion–Arginine Complexes: Evidence for Anion-Induced Zwitterion Formation in Gas-Phase Arginine

Abstract: We report the first low-energy collisional-induced dissociation studies of the X(-)·arginine (X(-) = F(-), Cl(-), Br(-), I(-), NO(3)(-), ClO(3)(-)) series of clusters to investigate the novel phenomenom of anion-induced zwitterion formation in a gas-phase amino acid. Fragmentation of the small halide ion clusters (F(-)·arginine and Cl(-)·arginine) is dominated by deprotonation of the arginine, whereas the major fragmentation channel for the largest ion clusters (I(-)·arginine and ClO(3)(-)·arginine) correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…10,11 Anionic interactions may also stabilize isolated amino acid zwitterions. 12,13 These naturally adopt canonical isomers in the gas phase, 14,15 but oxalate and malonate are computationally predicted to cluster with zwitterionic glycine, 16 and halide-bound ArgX À zwitterions have been confirmed by infrared multiple photon dissociation (IRMPD) spectroscopy. 17 The current work similarly uses IRMPD spectroscopy to identify the structures of PheX À complexes (X = Cl À and Br À ) and five fluorinated derivatives (3-and 4-fluoro, 2,5-and 3,5-difluoro, and pentafluoro).…”
Section: Introductionmentioning
confidence: 97%
“…10,11 Anionic interactions may also stabilize isolated amino acid zwitterions. 12,13 These naturally adopt canonical isomers in the gas phase, 14,15 but oxalate and malonate are computationally predicted to cluster with zwitterionic glycine, 16 and halide-bound ArgX À zwitterions have been confirmed by infrared multiple photon dissociation (IRMPD) spectroscopy. 17 The current work similarly uses IRMPD spectroscopy to identify the structures of PheX À complexes (X = Cl À and Br À ) and five fluorinated derivatives (3-and 4-fluoro, 2,5-and 3,5-difluoro, and pentafluoro).…”
Section: Introductionmentioning
confidence: 97%
“…However, anion complexation also relies on hydrogen bonding, iondipole interactions, and hydrophobic effects which in principle may also preferentially stabilize zwitterionic forms relative to their neutral, canonical counterparts. 3 In addition, other non-covalent contacts, including anion-π effects favored between π-acidic arenes and charge-diffuse anions, may contribute in stabilizing negatively charged adducts of (aromatic) amino acids. Recently, Infrared Multiple Photon Dissociation (IRMPD) spectroscopy, [4][5][6][7] a powerful tool to identify the structural and electronic features of various ionic species in the gas phase, [8][9][10][11][12][13][14] including mono- [15][16] and divalent- 17 metal-bound amino acids, has revealed canonical structures for halide adducts of glutamic acid, histidine, and phenylalanine.…”
Section: Introductionmentioning
confidence: 99%
“…Amino acids (AAs) are the building blocks of proteins and play a crucial role in living cells and biological processes. , All 20 proteinogenic AAs adopt zwitterionic structures with the N-terminus protonated and the C-terminus deprotonated under typical physiological conditions, whereas they exist in their canonical forms in the gas phase. Previous studies have shown that the gaseous zwitterionic forms of AAs can be stabilized upon solvation and exist in AA-ion clusters, illustrating the remarkable molecular binding forces exerted by solvents and ions on AA structures. AA-ion complexes are tractable both by first principle calculations and detailed spectroscopic characterizations, making them attractive models for probing fundamental intermolecular interactions important to the understanding of protein and ion function under biological settings.…”
mentioning
confidence: 99%
“…Gas phase ion spectroscopy accompanied by high-level ab initio computations has proven to be a powerful means for determining biomolecule-ion structures, but there are significant challenges regarding (1) how to experimentally populate energized isomers and (2) how to obtain spectroscopic signatures for distinguishing different but similar structures. We recently demonstrated in the Gly·I – case study that cryogenic “iodide-tagging” negative ion photoelectron spectroscopy (NIPES) coupled with an electrospray ionization (ESI) source is an effective approach for this purpose .…”
mentioning
confidence: 99%